The cancer-associated SF3B1 K700E spliceosome mutation confers enhanced sensitivity to BV-6-induced cytotoxicity - Lydia E. Roets; Jaine K. Blayney; Hayley P. McMillan; Patrick J. Preston; Alexander M. Mutch; Ken I. Mills; Kienan I. Savage; Katrina M. Lappin (Cell Death and Disease)
Abstract Recurrent somatic mutations in the key spliceosome component, SF3B1, have been identified at various frequencies across several cancer types. The most common hotspot mutation is the K700E missense mutation, and while its effects on splicing have been well characterised at the molecular level, the mis-spliced genes that contribute to cancer progression and/or dictate responses to therapy are still unclear. Here, we used we use cell line modelling to assess the impact of the SF3B1K700E mutation on the cellular response to various apoptosis-inducing agents. Our data suggest that the SF3B1K700E mutation leads to reduced cFLIP levels, along with defects in the splicing and translation of BCL2, causing a shift in the balance of pro- and anti-apoptotic genes and proteins, which confers greater sensitivity to the bivalent SMAC mimetic, BV-6. As such, BV-6 may represent a therapeutic opportunity for patients with SF3B1 mutant cancers.